Pemanfaatan Media Pembelajaran Digital Terintegrasi Berbasis Google Sites untuk Meningkatkan Pemahaman Siswa Sekolah Dasar terhadap Kegiatan Ekonomi: The Use of Google Sites-Based Integrated Digital Learning Media to Improve Elementary Students’ Understanding of Economic Activities - Sita Desviana; Muna, Siti Maemunah Nurul; Wahyuni, Ghina Aulia Rohmah; Nayla, Naya; Shafarina, Raisha Gysella; Nugraha, Rana Gustian (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2025)
This study aims to examine the effectiveness of Google Sites–based digital learning media in improving fifth-grade students’ understanding of economic activities, including production, distribution, and consumption. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, implemented in two cycles consisting of planning, action, observation, and reflection. In Cycle I, the Inquiry Learning Model was applied to facilitate student exploration through images, videos, and interactive tasks integrated into Google Sites. The results of the first cycle indicated an improvement in comprehension; however, several students still faced difficulties in connecting the roles of economic actors. Improvements were made in Cycle II by implementing the Role-Playing model to provide concrete learning experiences through dramatization of economic processes. The findings showed a consistent increase in learning outcomes from pre-test to post-test in both cycles, along with higher participation and engagement. Overall, the integration of Google Sites with appropriate learning models proved effective in enhancing elementary students’ conceptual understanding of economic activities.